2020
DOI: 10.1186/s43046-020-00041-5
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-randomized clinical trial: virtual reality versus proprioceptive neuromuscular facilitation for postmastectomy lymphedema

Abstract: Background Postmastectomy lymphedema can be considered the main cause of upper extremity functional impairment in patients with breast cancer. Fatigue, pain, and limited range of motion are common symptoms. If left untreated, lymphedema causes cellulitis, which can lead to gangrene in rare cases. This study was carried out to identify and compare the therapeutic advantages of virtual reality-based exercises and proprioceptive neuromuscular facilitation for postmastectomy lymphedema. Thus, a quasi-randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(82 citation statements)
references
References 18 publications
0
82
0
Order By: Relevance
“…However, the type of cancer in each study differs considerably, as shown in Table II. Approximately, 23% of the papers were focused on breast cancer treatments [22], [23], [26], [27], [28], [31], [35], [37], [39], [41] followed by blood cancer (e.g., leukaemia, lymphoblastic, etc.) (12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the type of cancer in each study differs considerably, as shown in Table II. Approximately, 23% of the papers were focused on breast cancer treatments [22], [23], [26], [27], [28], [31], [35], [37], [39], [41] followed by blood cancer (e.g., leukaemia, lymphoblastic, etc.) (12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40].…”
Section: Resultsmentioning
confidence: 99%
“…Further to the type of cancer, almost half of the studies examined the effectiveness of VR in accordance to pain (65%). Most focused on Acute-Procedural Pain (38%) [21], [24], [25], [26], [27], [29], [36], [37], [41], [42]. The pain was induced via venipuncture, surgery and biopsies, while the remaining 15% cases of pain, as a result of chronic conditions [24], [31], [39], [40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations